Artificially sweetened beverages and the response to the global obesity crisis - Borges,MC; Louzada,ML; de,Sá TH; Laverty,AA; Parra,DC; Garzillo,JM; Monteiro,CA; Millett,C (Plos Medicine, 2017)
In March 2015, the World Health Organization (WHO) published revised guidelines onsugar intake that call on national governments to institute policies to reduce sugarintake and increase the scope for regulation of sugar-sweetened beverages (SSBs).• In face of the growing threat of regulatory action on SSBs, transnational beverage companiesare responding in multiple ways, including investing in the formulation and salesof artificially sweetened beverages (ASBs), promoted as healthier alternatives to SSBs.• The absence of consistent evidence to support the role of ASBs in preventing weightgain and the lack of studies on other long-term effects on health strengthen the positionthat ASBs should not be promoted as part of a healthy diet.• The promotion of ASBs must be discussed in a broader context of the additional potentialimpacts on health and the environment. In addition, a more robust evidence base,free of conflicts of interest, is needed.